Effect of Holder pasteurization on macronutrients and immunoglobulin profile of pooled donor human milk. (17th September 2019) - Adhisivam, B.; Vishnu Bhat, B.; Rao, Krishna; Kingsley, S. M.; Plakkal, Nishad; Palanivel, C.
Abstract: Objective: The objective of this study was to study the effect of Holder pasteurization on macronutrients and immunoglobulin profile of pooled donor human milk. Methods: This descriptive study was conducted in a Human Milk Bank of a tertiary care teaching institute in south India. Thirty random paired pooled donor human milk samples (before and after pasteurization) were analyzed for macronutrients (protein, fat, carbohydrates) using infrared spectroscopy. Similarly, immunoglobulin profile (IgA and IgG) before and after pasteurization was quantified using ELISA. Results: The mean values of protein, fat, and carbohydrates in pooled donor milk pre-pasteurization were 1.6, 3.6, and 6.1 g/dl compared with post-pasteurization values 1.4, 2.7, and 5.9 g/dl, respectively. Pasteurization reduced protein, fat, and energy content of pooled donor milk by 12.5%, 25%, and 16%, respectively. However, carbohydrates were not significantly reduced. Pasteurization decreased IgA by 30% and IgG by 60%. Conclusion: Holder pasteurization of pooled donor human milk decreases protein, fat, and energy content and also reduces the levels of IgA and IgG.